Congenital cytomegalovirus infection is associated with high maternal socio‐economic status and corresponding low maternal cytomegalovirus seropositivity. (5th March 2014) - Basha, James; Iwasenko, Jenna M; Robertson, Peter; Craig, Maria E; Rawlinson, William D
<x xml:space="preserve">Abstract</x> Aims Human cytomegalovirus (CMV) is the leading infectious cause of congenital infection in developed countries. Globally, CMV seropositivity has been associated with low socio‐economic status (SES); however, Australian data are lacking. Therefore, we examined the association between SES and CMV seroprevalence in children and pregnant women. Methods Three groups were examined: 1, a prospective cohort of Australian children aged 0–15 years (n = 220); 2, a clinic‐based sample of pregnant women (n = 778); and 3, a case series of infants and children (n = 219) with symptomatic congenital CMV infection. SES was determined using a postcode‐based score from the Australian Bureau of Statistics.Group 1 was recruited from endocrinology clinics and follow‐up at Prince of Wales Hospital and Children's Hospital at Westmead. Group 2 was recruited at the Royal Hospital for Women. Congenitally infected infants were identified through the Australian Paediatric Surveillance Unit. Results CMV seroprevalence among all children was 20% (95% confidence interval (CI) 15–25%), and there was no association with SES (P = 0.58). Seroprevalence among pregnant women was 57% (53–60%), and higher rates of CMV seropositivity were associated with lower SES (P < 0.001). More congenital CMV cases were reported in the highest socio‐economic groups (55%) than the lowest (9%) (P < 0.001). Conclusions A marked socio‐economic gradient in CMV seroprevalence is evident in Australian pregnant women and cases of congenital CMV but not in unselected Australian children. These findings highlight the importance of a community‐wide approach to CMV awareness and the potential for hygienic measures to reduce the burden of congenital CMV in Australia.